FRI0478 SEROLOGICAL AUTOIMMUNITY IN PATIENTS WITH RHEUMATIC IMMUNE-RELATED ADVERSE EVENTS: CORRELATION WITH SEVERITY AND TREATMENT. (13th June 2020) - Campochiaro, C.; Tomelleri, A.; Ferrara, R.; Lazzari, C.; De Luca, G.; Signorelli, D.; Bulotta, A.; Gregorc, V.; Garassino, M.; Dagna, L.
Abstract : Background: Immune checkpoint inhibitors (ICIs) can induce a variety of rheumatic immune-related adverse events (Rh-irAEs). Few data are available on which features can predict the occurrence of long-lasting and severe Rh-irAE Objectives: To describe the serological features associated with long-lasting and severe Rh-irAE. Methods: ICI-treated patients were identified. Patients' demographics, histotype of cancer, ICI, time interval from ICI start to Rh-irAE onset, characteristics of Rh-irAEs were recorded. Patients were tested for autoimmunity panel (a-IP): RF, ACPA, ANA, anti-SSA, anti-SSB, anti-Sm, anti-RNP, anti-Jo1, ANCA, ASMA, AMA, anti-dsDNA, anti-tireoglobulin, anti-tireoperoxidas, IgM and IgG anti-cardiolipin and anti-β2 glicoprotein I, crioglobulins. All patients were treated with steroids (CS). In case of flare of the Rh-irAE, csDMARDs or bDMARDs were started. Associations between a-IP status and need for DMARD start was evaluated. Non parametric tests were used. Results: 22 Rh-irAE were included (see Table 1 ). Median age at Rh-irAE onset was 70 (50 – 84) years. 2 patients (9%) had a personal history of psoriasis. Median time from ICI start to Rh-irAE onset was 5 (1 – 26) months. 11 patients (50%) developed 1 Rh-irAE, 10 (45.4%) 2 and 1 (4.5%) 3. The most frequent were arthritis (A, 14, 63.6%), cutaneous vasculitis (CV, 5, 22.7%), PMR-like (4, 18.2%), polymyositis (PM, 4, 18.2%), myocarditis (Myo, 3, 13.6%) and dermatomyositis (DM, 2, 9.1%). Median initial prednisone dose was 25 (10 – 75) mg daily. In 14 patients (63.6%) a csDMARD was started upon steroids tapering. 9 patients (41%) were treated with methotrexate (MTX, 4, 18.2%) with hydroxychloroquine (HCQ, 2, 9.1%) with mycophenolate (MMF, 2, 9.1%) with colchicine (colch). 6 patients were treated with bDMARDs. 3 patients (50%) were treated with anakinra (ANK), 2 (33.3%) with IVIG and 3 (50%) with tocilizumab (TCZ). 13 patients (59.1%) were a-IP+. A significantly higher percentage of a-IP+ patients received DMARDs (11, 84.6%) compared to a-IP- patients (2, 22.2%, p = 0.0007). A significantly higher percentage of a-IP+ patients were treated with bDMARDs (5, 38.5%) compared to a-IP- patients (0, 0%, p = 0.05). We analysed whether in csDMARD-treated patients the need for bDMARDs was higher in a-IP+ but we found no statistical significance (45.4% vs 0%, p = 0.487). Conclusion: The presence of serological autoimmunity might be helpful in detecting patients with Rh-irAEs refractory to steroid therapy. Disclosure of Interests: Corrado Campochiaro Speakers bureau: Novartis, Pfizer, Roche, GSK, SOBI, Alessandro Tomelleri: None declared, Roberto Ferrara: None declared, Chiara Lazzari: None declared, Giacomo De Luca Speakers bureau: SOBI, Novartis, Celgene, Pfizer, MSD, Diego Signorelli: None declared, Alessandra Bulotta: None declared, Vanesa Gregorc: None declared, Marina Garassino: None declared, Lorenzo Dagna Grant/research support from: Abbvie, BMS, Celgene, Janssen, MSD, Mundipharma Pharmaceuticals, Novartis, Pfizer, Roche, SG, SOBI, Consultant of: Abbvie, Amgen, Biogen, BMS, Celltrion, Novartis, Pfizer, Roche, SG, and SOBI